Reading Fluency As a Predictor of School Outcomes across Grades 4–9 - Bigozzi, Lucia; Tarchi, Christian; Vagnoli, Linda; Valente, Elena; Pinto, Giuliana (Frontiers in Psychology, 2017)
This study analyzed the predictive relationship between reading fluency and school outcomes across school levels (primary, secondary, and high school), after controlling on the effect of reading comprehension. The sample included 489 children attending Italian primary (grades 4 and 5), secondary (grades 6 and 8), and high schools (grade 9). Students' reading fluency and comprehension were examined with a standardized reading achievement test. At the end of the school year, we requested the school reports of each participant. According to our data, reading fluency predicted all school marks in all literacy-based subjects, with reading rapidity being the most important predictor. School level did not moderate the relationship between reading fluency and school outcomes, confirming the importance of effortless and automatized reading even in higher school levels. Overall this study emphasizes the importance of identifying evidence-based tasks that can be administered in a short time and to many different individuals, which are easy to create, and are linked to school outcomes.